Do Backward Associations Have Anything to Say About Language? - Chartier, Thomas F.; Dautriche, Isabelle (Cognitive science, 2023)
In this letter, we argue against a recurring idea that early word learning in infants is related to the low‐level capacity for backward associations—a notion that suggests a cognitive gap with other animal species. Because backward associations entail the formation of bidirectional associations between sequentially perceived stimulus pairs, they seemingly mirror the label‐referent bidirectional mental relations underlying the lexicon of natural language. This appealing but spurious resemblance has led to various speculations on language acquisition, in particular regarding early word learning, which we deconstruct here.